On k-Switching of Mappings on Finite Fields - Evoyan, Mikayel G.; Kyuregyan, Gohar M.; Kyuregyan, Melsik K. (Mathematical Problems of Computer Science, 2021)
The switching construction was used in several recent papers to construct special mappings on finite fields. In this paper we generalize the concept of switching to a k-switching with 1 ≤ k ≤ n. We present some general properties of k-switching and describe permutations produced using k-switching.